Assessing the use of PSA videos: Challenges and benefits for technical university students - Hamizah, Zahari; Rosnani, Ismail; Ezihaslinda, Ngah (UPM, 2024)
Visual communication has appeared as a powerful tool to communicate ideas that will appeal to a variety of people in today’s increasingly media-driven world. Public Service Announcement (PSA), in particular, has become one of the effective mediums for raising awareness on social issues, promoting behavioural change, and educating the public. Elliott (2020) mentioned that incorporating PSA-based activities requires students to participate in active learning, inspiring them to analyse problems, gather information, and consider specific purpose and audience. Recognizing this platform's potential in educational settings, integrating PSA video creation as part of assessments would encourage students to improve their language performance and foster other additional skills. According to Greenblatt & McDonald (2022), a group work project to create PSA videos effectively assessed language skills, offering opportunities to improve English proficiency, and engaging in communicative activities.